Evaluation of a Computer-Based HIV Education Program for Adults Living with HIV. - Subramaniam, Shrinidhi; Getty, Carol-Ann; Holtyn, August F.; Rodewald, Andrew; Katz, Brian; Jarvis, Brantley P.; Leoutsakos, Jeannie-Marie S.; Fingerhood, Michael; Silverman, Kenneth (AIDS & Behavior, 2019)
This study evaluated a computer-delivered HIV and antiretroviral treatment education program in adults (N = 102) living with detectable HIV viral loads (> 200 copies/mL). The self-paced program provided immediate feedback for responses and financial incentives for responding correctly. The program was divided into three courses and a test of content from all three courses was delivered before and after participants completed each course. Test scores on the content delivered in Courses 1, 2 and 3 improved only after participants completed training on the relevant course. Initial test scores were positively correlated with health literacy and academic achievement; were negatively correlated with viral load; and were lowest for participants living in poverty. Education, academic achievement, and health literacy were related to how much participants learned following each course. Computer-based education is a convenient, effective approach to promoting an understanding of HIV and its treatment.